2014
DOI: 10.1016/j.fob.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNA501‐5p affects the aggressiveness of clear cell renal carcinoma

Abstract: HighlightsLow expression of miR501-5p correlates with good prognosis for patients with ccRCC.miRNA501-5p downregulation stimulates apoptosis by p53 activation.miR501-5p upregulation promotes cell proliferation and survival.Increased cell growth occurs by activation of mTOR kinase and MDM2 expression.This miRNA modulates apoptosis/cell growth, making it a prognostic biomarker for ccRCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…These molecules can differentiate ccRCC from papillary and chromophobe histologies (5) and have been associated with RCC metastasis (6)(7)(8) and aggressiveness (9)(10)(11)(12)(13)(14)(15). The Cancer Genome Atlas (TCGA) project on ccRCC showed that unsupervised analysis of miRNA expression can classify tumors into 4 distinct clusters of different survival, with miR-21 showing the strongest correlation with poor overall survival (OS) (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules can differentiate ccRCC from papillary and chromophobe histologies (5) and have been associated with RCC metastasis (6)(7)(8) and aggressiveness (9)(10)(11)(12)(13)(14)(15). The Cancer Genome Atlas (TCGA) project on ccRCC showed that unsupervised analysis of miRNA expression can classify tumors into 4 distinct clusters of different survival, with miR-21 showing the strongest correlation with poor overall survival (OS) (9).…”
Section: Introductionmentioning
confidence: 99%
“…The Cancer Genome Atlas (TCGA) project on ccRCC showed that unsupervised analysis of miRNA expression can classify tumors into 4 distinct clusters of different survival, with miR-21 showing the strongest correlation with poor overall survival (OS) (9). Studies with a smaller number of samples have also proposed miRNA signatures as markers of aggressive ccRCC (10)(11)(12)(13)(14)(15), suggesting an important role for miRNAs in prognosis. However, these studies mentioned…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments have shown that miRNAs could function as important regulators in the carcinogenesis of renal cancer. For example, miR-133b inhibited cell proliferation, migration and invasion by targeting matrix metallopeptidase-9 (22), and downregulating miR-501-5p induced increases in caspase-3 activity and p53 expression, as well as decreasing mTOR activation, which leads to the stimulation of the apoptotic pathway (23). In addition, miRNAs may also be promising biomarkers for RCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These clustered miRNAs are part of the miR-500 and miR-132 miRNA family. There is evidence reporting that miR-500 family take part in kidney cancer [45,46,44]. Genomic locations of these synergistic miR-500 family miRNAs are illustrated in Figure 5.…”
Section: Triplets Coded Close On the Genomementioning
confidence: 99%